Effect of varying levels of products containing medium chain fatty acids (MCFA) compared to zinc oxide (ZnO) and carbadox on nursery pig performance - Scarbrough, Elizabeth L.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
This study evaluated whether products containing medium chain fatty acids (MCFA) are able to replace antibiotics and feed additives, specifically ZnO and carbadox, in increasing nursery pig performance. In this 35 d experiment, there were 360 weanling pigs (DNA 200x400; 5.4 ± 0.07 kg) testing 6 different treatments: 1) control; 2) 50 g/ton carbadox; 3) d 0 to d 7: 3,000 ppm P1/ d-8 to d-19:1,500 ppm P2 ZnO; 4) 1% blend of C6, C8, C10; 5) 1% Feed Energy R2 (Feed Energy Corp., Des Moines, IA); 6) 1% FORMI GML (ADDCON, Bitterfield-Wolfen, Germany). There were 10 replicates of 6 pigs/pen in a completely randomized pattern. From d 1 to d 19 pigs were fed the experimental treatments and a control from d 20 to d 35. The data collected weekly were pig and feeder weights. The experimental unit for growth performance was each pen, but for the blood and fecal it was individual pig. This study used the GLIMMIX procedure of SAS (SAS Inst. 9.4; Cary, NC). In the overall treatment data (d 0 to d 19), pigs fed ZnO had improved average daily gain (ADG) (P =0.0001) and average daily feed intake (ADFI) (P =0.0004) than those fed the R2 and control formulas which were statistically similar to each other. In the overall data (P =0.012) of ADG, pigs fed ZnO were significantly more efficient than those fed R2 or the control. In the overall ADFI calculated (P =0.001), pigs fed ZnO and carbadox consumed significantly more feed than pigs fed the R2 diet. The FORMI and C6:C8:C10 diets were found to have intermediate performance. Therefore, MCFA were not able to be proven more efficient for nursery pig growth performance than ZnO or carbadox.
Keywords: Spring 2019